Effects of distilled Phaseoli Semen rubra Herbal-Acupuncture on lipid composition, liver function, antioxidant capacity and molecular biological aspects in obese rats induced high fat diet - Ji, Jun Hwan; Lee Jun Mu (Korean Pharmacopuncture Institute, 2005)
Effects of Phaseoli Semen rubra Herbal-acupuncture at zusanli(ST-36), Quchi(LI-11) and Sanyinjiao(Sp-6) on lipid composition, liver function, oxidative capacity and molecular biological aspects were investigate in high fat diet induced obese rats. Forty male Sprague-Dawley rats weighing about 400g were divided into 4 groups according to body weight and raised four weeks with control, zusanli(ST-36), Quchi(LI-11) and Sanyinjiao(Sp-6) Herbal-acupuncture groups. 1. Plasma total cholesterol and LDL-cholesterol showed a low values in the (ST-36) and (LI-11) Herbal-acupuncture groups and HDL- cholesterol showed a high values in the (ST-36) Herbal-acupuncture groups. 2. Plasma triglyceride and glucose showed a low values in the (ST-36) and (LI-11) Herbal-acupuncture groups. 3. The contents of plasma free fatty acids showed a tendence to decrease in the Herbal-acupuncture groups, however in the Herbal-acupuncture groups, the values showed no significantly different. 4. The activities of AST and ALT showed no significantly different in all treatment groups. 5. The contents of plasma β-lipoprotein and free fatty acids showed a tendency to decrease in the Herbal-acupuncture groups compared to those of control group. In the Herbal-acupuncture groups, the values of (ST-36) and (LI-11) Herbal-acupuncture groups showed a low in the acupuncture groups. 6. Liver total cholesterol and triglyceride showed a low values in the (ST-36) and (LI-11) Herbal-acupuncture groups. 7. Contents of plasma TBARS showed a low values in the (ST-36) and (LI-11) Herbal-acupuncture groups, however contents of liver TBARS showed no significantly different among treatment groups. 8. Values of liver glutathione peroxidase and catalase activity showed a tendency to increase in the (ST-36) and (LI-11) Herbal-acupuncture groups. Values of liver super oxide dismutase activity showed a high in the (ST-36) Herbal-acupuncture groups compared to those of other groups. 9. Expression of apo-B mRNA in liver cell showed a low in (ST-36) Herbal-acupuncture groups, however expression of apo-E mRNA showed a high in Herbal-acupuncture groups and TNF-α mRNA in adipose cell showed no different among all the treatment groups. Expression of Leptin mRNA showed a tendance to decrease in (ST-36) Herbal- acupuncture group. 10. Histological character of liver, those of (ST-36) Herbal- acupuncture group showed a good, however other treatment groups showed slight vasodilation and slight fat accumulation. These results indicated that Phaseoli Semen rubra Herbal-acupuncture at (ST-36) and (LI-11) suppressed adipose tissue mass and lipid peroxidation and increased antioxidant system.